O olhar dos cronistas no jornal da serra, de Carazinho-RS : "respingos" e "cousas da cidade" (1930-1945) - Sawoff, Raquel Inês Zuglianello (2007)
The aim of this study is to analyze, through the chronicles Respingos, by Canuto de Souza and Cousas da Cidade, by Afonso Pedro, published on Jornal da Serra: Carazinho/RS, the local reality of the 1930 s and 1940 s, while trying to understand the mediation constructed by such chronicles, both developed by Canuto, a political actor who used his newspaper as a tribune, i.e., an instrument to legitimate dispute and power. The study was focused on quite a troubled context as, within the local sphere, there was pre and post-emancipatory turmoil and, within the national sphere, there were all sorts of pressure and denounce that characterized the first Vargas government, while in the international sphere there was World War II. Thus, attempts were made so as to understand the interference of such socio-political structure upon the everyday life of people in Carazinho, taking into account the plots that were created, as in the region of the study the German ethnicity has been, since the beginning of its foundation, an important feature. Thus, attempts were made so as to analyze how that trait was understood by both writers, considering that, in the 1930 s, the Jornal da Serra was the only newspaper in the city showing open resistance to the local politics, represented by Albino Hillebrand, particularly following the disagreements between Getúlio Vargas and Flores da Cunha after 1937